Strategia marki w budowaniu tożsamości miasta: Brand strategy in building a city’s identity - Grzyb, Artur (Management and Administration Journal, 2021)
The identity of the brand of a place is its key image which can be clearly communicated outside. It leads to creating a capital, expressed not only by the loyalty of consumers, but also price bonus for goods originating from the region or city. Both the identity and the brand capital are closely related to the concept of the image, whose significance can be reduced to a short statement that places can transform rapidly, but the opinion about them may not be changed for years, and even decades. The described model is based on three basic levels in which specific tasks are carried out, often related to each other, and systematizing the process. The stages are defined as: diagnostic, exploration, and strategic.